Improving sustainability of aquaculture in Europe: Stakeholder dialogues on Integrated Multi-trophic Aquaculture (IMTA). Issue 55 (January 2016) - Alexander, K.A.; Angel, D.; Freeman, S.; Israel, D.; Johansen, J.; Kletou, D.; Meland, M.; Pecorino, D.; Rebours, C.; Rousou, M.; Shorten, M.; Potts, T.
Highlights: Levels of awareness of IMTA were variable across stakeholder groups and across countries. Positive aspects of IMTA included environmental benefits such as waste utilisation and economic benefits. Negative impacts of IMTA identified as spatial and location issues, disease outbreak potential, food safety and containment. IMTA may contribute to improving the image of the aquaculture industry. Abstract: Research into stakeholder perceptions of conventional aquaculture has focused upon issues such as risk, impact on other users of marine space, and the factors influencing consumers. However, some of these issues may become redundant with new aquaculture practices such as Integrated Multi-trophic Aquaculture (IMTA). For practices such as IMTA to realise their potential they must be socially acceptable and this may depend on satisfying key stakeholders. This study used in-depth interviews to identify potential concerns of stakeholders as well as perceived benefits in relation to the development of IMTA to a commercial level of production. A total of 44 interviews were conducted across 12 stakeholder groups in six countries: Cyprus, Ireland, Israel, Italy, Norway and Scotland. Levels of awareness and understanding of IMTA were mixed across stakeholder groups and across countries. Concerns were raised including: spatial location issues, food safety and disease. Perceived benefits of IMTA included: waste utilisation, minimisation of impacts to the benthos and the filtering of sea lice larvae. Also recognised as important was the creation of new income streams. The results showed that some issues/benefits were more important in certain countries. Risks to the environment, risks arising from governance and risks to the industry itself were raised, but stakeholders felt that these sources of risk could be addressed by research studies, education and changes to legislation. Stakeholders also believed that IMTA could contribute to improving the image of the aquaculture industry. For IMTA to successfully move forward from pilot scale to commercial scale development, it is imperative that the issues raised in this study form priorities for reform and action.